Assessing rural households’ biomass consumption patterns in three Upazilas in Khulna district of Bangladesh - Rahul Biswas; Arifa Sharmin; Md. Ashaduzzaman; Md. Akramul Islam (SN Applied Sciences, 2023)
Abstract In developing countries, rural households instinctively burn huge amounts of biomass fuel, which has become a concern at present. In this study, an attempt has been made to assess the consumption pattern of biomass fuel in relation to socio-economic factors in rural households in the three upazilas (subdistricts) in Khulna district of Bangladesh. The consumption pattern of biomass fuel was assessed by multistage random sampling techniques with a semi-structured questionnaire. The study revealed that households incorporate a variety of fuel sources, of which 97% use various types of biomass fuel, e.g., firewood, leaves and twigs, coconut shell and coir, crop residues, cow dung, etc. The average monthly household biomass fuel consumption was 193 kg, with a monthly expenditure of 5.86 USD. The largest share of biomass fuel was derived from firewood, which amounted to 105 kg per month. The middle income group and Kacha (clay) type households consume more biomass than other types of households. The major sources of biomass fuel were found in their home gardens and agricultural lands. These biomass fuels are mainly used for domestic cooking, and most of the households in the study area used general stoves. Among commonly available species, ten firewood species were identified as the most preferred by the majority of households in the study area. Insights from our research may be utilized to promote accessibility to clean energy for households in Bangladesh and other countries alike.